Admissibility of use in proving the actual data that has been obtained using the polygraph - Мотлях, Олександр Іванович; Тодосієнко, Анна Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
This article discusses the use of the polygraph and received with the help of data proving, as one of the possible evidence in criminal proceedings. The features of this activity based on scientific approaches of domestic and foreign scholars.